Symplectic Methods in Deep Learning - Maslovskaya, Sofya; Ober-Blöbaum, Sina (IFAC-PapersOnLine)

Inverse optimal control problem in the non autonomous linear-quadratic case - Jean, Frédéric; Maslovskaya, Sofya

ICILS 2023 #NRW. Computer- und informationsbezogene Kompetenzen und Kompetenzen im Bereich Computational Thinking von Schüler*innen in Nordrhein-Westfalen im internationalen Vergleich - Drossel, Kerstin; Eickelmann, Birgit; Niemann, Jan; Niggemeier, Johannes Bernd

Siebter Oktober Dreiundzwanzig. Antizionismus und Identitätspolitik

An approach for a metamodel-based consideration of a process chain when mechanically joining sheet metal components - Neumann, Jonas; Kappis, Lukas; Lontsi, Seraphin Tsi-Nda; Ludwig, Jean-Patrick; Ramaiya, Umang Bharatkumar; Scharr, Christian; Vallaster, Eva; Flügge, Wilko; Meschut, Gerson; Merklein, Marion (15th Forming Technology Forum)
Batch and process fluctuations during the fabrication of sheet metal components result in discrepancies in the resulting component properties, affecting subsequent process steps and potentially leading to production rejects. Consequently, the identification of deviations and knowledge of the effects of fluctuations are crucial for achieving consistently high product quality, reducing waste and thus increasing resource efficiency of production processes through countermeasures derived from this. The approach presented to address this is the use of data-driven metamodeling to map entire process chains and predict process parameters in order to compensate for process and batch fluctuation. The investigated process chain consists of the sub-processes deep drawing, clamping and clinching. For each process step, relevant input and output variables are identified, numerical simulation models are created, and subsequently validated. Variant simulations of the sub-processes are conducted and evaluated to generate a database for the metamodeling of the individual process steps. Machine learning techniques are utilized for the automated selection and optimization of learning methods to create models that depict the relationships between input and output variables. Finally, the models for the sub-processes are linked together to form a superordinate metamodel for the entire process chain, with the aim to make inline-process adaptations possible.<br

Parameterized complexity of weighted team definability - Kontinen, Juha; Mahmood, Yasir; Meier, Arne; Vollmer, Heribert (Mathematical Structures in Computer Science)
Abstract In this article, we study the complexity of weighted team definability for logics with team semantics. This problem is a natural analog of one of the most studied problems in parameterized complexity, the notion of weighted Fagin-definability, which is formulated in terms of satisfaction of first-order formulas with free relation variables. We focus on the parameterized complexity of weighted team definability for a fixed formula $φ$ of central team-based logics. Given a first-order structure $\mathcal{A}$ and the parameter value $k\in \mathbb N$ as input, the question is to determine whether $\mathcal{A},T\models φ$ for some team T of size k . We show several results on the complexity of this problem for dependence, independence, and inclusion logic formulas. Moreover, we also relate the complexity of weighted team definability to the complexity classes in the well-known W-hierarchy as well as paraNP.

Die Pflicht, up-to-date zu sein. Adressierungen (werdender) Eltern durch Schwangerschafts- und Erziehungsapps - Sänger, Eva; Langer, Antje; Carstensen, Tanja (GENDER – Zeitschrift für Geschlecht, Kultur und Gesellschaft)
Software-Apps sind inzwischen zentraler Bestandteil des alltäglichen Lebens. Vor dem Hintergrund dieser umfassenden Digitalisierung des Sozialen fragt der Beitrag danach, welche Selbstverhältnisse und generationalen Beziehungen durch Erziehungs- und Schwangerschaftsapps konstruiert und adressiert werden, welche normierenden Effekte diese Apps haben und welche Themen ausgeklammert werden. Der Beitrag beruht auf einer qualitativen Analyse von 55 Inhaltsbeschreibungen von Schwangerschafts- und Erziehungsapps aus App-Stores. Wir zeigen, dass neben hetero- und geschlechternormativen Adressierungen Schwangere und Eltern als vorausschauende Subjekte adressiert werden, die im Sinne einer antizipatorischen Risikologik insbesondere mit einem Regime des Upto- Date- bzw. Alert-sein-Müssens und einer ‚Pflicht zum Wissen‘ konfrontiert sind. Der Handlungsdruck, der auf diese Weise erzeugt wird, geht zugleich mit dem Versprechen einher, diese Aufgaben an die App abgeben zu können.

Covariational reasoning in Bayesian situations - Büchter, Theresa; Eichler, Andreas; Böcherer-Linder, Katharina; Vogel, Markus; Binder, Karin; Krauss, Stefan; Steib, Nicole (Educational Studies in Mathematics)
Abstract Previous studies on Bayesian situations, in which probabilistic information is used to update the probability of a hypothesis, have often focused on the calculation of a posterior probability. We argue that for an in-depth understanding of Bayesian situations, it is (apart from mere calculation) also necessary to be able to evaluate the effect of changes of parameters in the Bayesian situation and the consequences, e.g., for the posterior probability. Thus, by understanding Bayes’ formula as a function, the concept of covariation is introduced as an extension of conventional Bayesian reasoning, and covariational reasoning in Bayesian situations is studied. Prospective teachers ( N =173) for primary ( N =112) and secondary ( N =61) school from two German universities participated in the study and reasoned about covariation in Bayesian situations. In a mixed-methods approach, firstly, the elaborateness of prospective teachers’ covariational reasoning is assessed by analysing the arguments qualitatively, using an adaption of the Structure of Observed Learning Outcome (SOLO) taxonomy. Secondly, the influence of possibly supportive variables on covariational reasoning is analysed quantitatively by checking whether (i) the changed parameter in the Bayesian situation (false-positive rate, true-positive rate or base rate), (ii) the visualisation depicting the Bayesian situation (double-tree vs. unit square) or (iii) the calculation (correct or incorrect) influences the SOLO level. The results show that among these three variables, only the changed parameter seems to influence the covariational reasoning. Implications are discussed.

How to teach Bayesian reasoning: An empirical study comparing four different probability training courses - Steib, Nicole; Büchter, Theresa; Eichler, Andreas; Binder, Karin; Krauss, Stefan; Böcherer-Linder, Katharina; Vogel, Markus; Hilbert, Sven (Learning and Instruction)

Frauenemanzipation in islamischen Ländern. Vom 19. Jahrhundert bis in die Gegenwart (Ariadne. Forum für Frauen- und Geschlechtergeschichte)

Vom foto-sozialen Graph zum Story-Format: Über die Institutionalisierung sozialmedialer Infrastruktur aus dem Geiste der Fotografie - Schulz, Christian (Die Fotografie und ihre Institutionen. Von der Lehrsammlung zum Bundesinstitut)

Automatically deriving test cases from safety-security dependencies - Trentinaglia, Roman; Fockel, Markus; Pukrop, Matthias; Schaeffer, Tobias (22th escar Europe : The World’s Leading Automotive Cyber Security Conference : Embedded Security in Cars (Dortmund, 19. - 20.11.2024))

The new TISTRAQ process: Solution treatment with rapid quenching and annealing for Ti-6Al-4V sheet metal part forming - investigation on heat transfer coefficient and influence on cooling rates - Kaiser, Maximilian Alexander; Höschen, Fabian; Pfeffer, Nina; Merten, Mathias; Meyer, Thomas; Marten, Thorsten; Rockicki, Pawel; Höppel, Heinz Werner; Tröster, Thomas (IOM3. Chapter 14: Forming, Machining & Joining [version 1; not peer reviewed])
Within the current energy and environmental crisis, new material- and energy-saving processes are needed. For this reason, this study focuses on the development of a new forming technology for Ti-6Al-4V sheet metal. It is based on combination of solution treatment by resistive heating with rapid tool-based quenching and subsequent annealing. This new “TISTRAQ” process is comparable with press-hardening already known for steels and hot die quenching known for aluminium alloys. One of the main influencing factors for this process is the heat transfer coefficient (HTC). It is an important driver for adjustment of basic parameters, as selection of tool material or the forming speed but also plays an important role while elaborating temperature distribution in the numerical model. Therefore, a new and unique test rig was developed to determine the HTC and to perform tool-based heat treatment at specimen level under laboratory conditions. The test rig was used to investigate the influence of the titanium-tool-lubricant system on HTC and cooling rate. Further the effect of heat treatment in the test rig and tool-based quenching on microstructure and mechanical properties was studied. To improve the prediction of the temperature distribution of the titanium during cooling, the HTC was integrated into the numerical process simulation
Keywords: Interfacial heat transfer coefficient; Ti-6Al-4V; nonisothermal forming; thermomechanical processing; TISTRAQ process

The new TISTRAQ process: Solution treatment with rapid quenching and annealing for Ti-6Al-4V sheet metal part forming - the effect of processing parameters on microstructure and mechanical properties - Pfeffer, Nina; Kaiser, Maximilian Alexander; Meyer, Thomas; Göken, Mathias; Höppel, Heinz Werner (IOM3. Chapter 14: Forming, Machining & Joining [version 1; not peer reviewed])
The phase and TTT diagrams of the Ti-6Al-4V system allow the development of a new forming process for a more energy- and materialefficient production of sheet metal parts. This new “TISTRAQ” process is composed of two steps. In terms of process technology, the first step is comparable to a direct press-hardening process already well known for steels. In this step, the Ti-6Al-4V sheet material is resistively heated to a temperature below β-transus Tβ and, after a very short holding time, simultaneously formed and quenched by use of water cooled tools. Thereby, the β phase undergoes a martensitic transformation. The second step is a subsequent short-time annealing, which leads to a hardening of the material. In this work, a new test rig using resistive heating technique was used in order to produce different solution treated and tool quenched (STQ) and subsequently annealed (STA) states. In this paper, the effects of heating rate, solution treatment temperature and holding time on microstructure and mechanical properties are addressed. For the characterisation, tensile testing and scanning electron microscopy were used. By the systematic variation of applied processing parameters, dominating effects on microstructure and mechanical properties were evaluated. For example, the solution treatment temperature was found to have a significant effect on microstructural features and characteristic strength and strain values. The obtained results reveal a high potential for future technical applications.
Keywords: Ti-6Al-4V; thermomechanical processing; resistive heating; quench-forming; process parameter-microstructure-properties relationship

Nebensätze in Nachhaltigkeitsberichten entdecken. Wie setzen Discounter Nebensätze in Nachhaltigkeitsberichten ein, um Nachhaltigkeitsabsichten zu erklären? - Dübbert, Alexander (Praxis Deutsch)
In Nachhaltigkeitsberichten legen Unternehmen Rechenschaft darüber ab, wie sie Maßnahmen für eine nachhaltige Entwicklung umsetzen. Gleichzeitig dienen solche Berichte der Imagepflege. Dieses Modell regt zu einer kritischen Reflexion an, wie mithilfe von Nebensätzen Nachhaltigkeitsabsichten erklärt werden.

Rolf Pohle and the failing of 1968. The life of a professional revolutionary in the ‘Red Decade’ and beyond - Vukadinovic, Vojin Sasa (Revolutionary Biographies in the 19th and 20th Century. Imperial – Inter/national – Decolonial)

Das It-Girl der Vernunft als Echo der Verhältnisse. Heide Heinz (1939–2022) - Vukadinovic, Vojin Sasa (Jahrbuch Sexualitäten 2024)

Workaround-to-Innovation — Exploring Bottom-Up Process Re-Design - Beverungen, Daniel; Bartelheimer, Christian; Assbrock, Agnes; Löhr, Bernd (European Conference on Information Systems (ECIS))

Social norms and individual climate protection activities: A survey experiment for Germany - Engler, Daniel; Gutsche, Gunnar; Simixhiu, Amantia; Ziegler, Andreas (Energy Economics)

RAWA. Der Kampf um Frauenbefreiung in Afghanistan - Vukadinovic, Vojin Sasa (Ariadne. Forum für Frauen- und Geschlechtergeschichte)